HUMAN RESOURCE DEVELOPMENT STRATEGIES FOR ENHANCING ORGANIZATIONAL PERFORMANCE IN THE DIGITAL ERA - Sigit Purwanto; Kasmin; Samudra Syarif Wahyu Hidayatullah; Dendy Tirtoadisuryo (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
The rapid advancement of digital technology has significantly transformed Human Resource Development (HRD) strategies, necessitating a shift towards innovative, technology-driven approaches. This study explores HRD strategies that enhance organizational performance in the digital era, focusing on talent acquisition, employee training and development, leadership development, performance management, and workplace culture. Organizations leverage digital tools such as artificial intelligence (AI)-driven applicant tracking systems, e-learning platforms, and virtual reality (VR) training to equip employees with essential digital competencies. Continuous learning and upskilling have become fundamental HRD components, enabling employees to adapt to evolving job roles and technological advancements. Leadership development in the digital age emphasizes digital literacy, agility, and transformational leadership to drive organizational success. Furthermore, performance management has evolved to incorporate real-time feedback, data analytics, and AI-driven evaluation techniques to optimize employee performance and engagement. A positive workplace culture fostering inclusivity, collaboration, and psychological safety is essential for sustaining innovation and productivity in digital work environments. This study employs a qualitative case study approach, utilizing in-depth interviews, participatory observation, and document analysis to examine HRD strategies in organizations undergoing digital transformation. Thematic analysis is used to identify key patterns contributing to organizational performance. Findings suggest that leveraging technology-driven HRD strategies enhances workforce adaptability, engagement, and overall business success. Organizations must continuously refine HRD practices to address emerging workforce trends, ethical considerations, and digital disruptions. Future research should investigate the long-term impact of digital HRD initiatives on employee satisfaction, retention, and organizational growth in a rapidly evolving business landscape.